The modern rugby player: Are we breeding giants and what are the consequences? - de Ridder, J. H.; van den Berg, P. H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
lthough physique is not the only factor determining success in sport, the modern game of rugby union has become a sport in which the physique of the players is a very important predictor of success. Furthermore the economic, political and social drivers of sporting success will act to select body types which conform more and more to an ideal morphology (Olds, 2001). In rugby, the rates of increase in height and body mass appear to have outstripped secular trends in the population from which these athletes are drawn. Therefore, the aim of this presentation is to answer the question resulting from existing anthropometric data, on whether we are busy breeding giants to play rugby and also to demonstrate the consequences this will have in future. Methods: The anthropometric data of the two most trendsetting studies on this topic were used. The first study was done on 1420 male rugby players drawn from 21 separate reports and communications between 1905 and 1999 on elite, national and state players (Olds, 2001). The second study was done on the national team of South Africa (Springboks). Data of 1349 rugby players between 1896 and 2004 were mapped (De Ridder & Meyer, 2007). Results: In the study done by Olds (2001) the results suggest that the rates of increase of body mass and BMI are well above those of the general population of young males. The study by De Ridder & Meyer (2007), suggest major shifts in the body size and shape of the rugby players, with the players as a whole becoming taller and heavier. The data also suggests that the rates of increase of body mass and BMI in the Springboks are well above those of the general population of young males. Discussion: Recognition of the importance of the demands of the game of rugby on the modern player`s physique, has led to a tendency for coaches to favour increasingly taller and heavier players, even for backline positions. Taken into consideration that rugby has one of the highest injury rates when compared to other team sports, this has the potential to result in a big increase in the incidence of injuries in rugby in the future. Conclusion The final rankings of the rugby teams at the recent 2011 World Cup in New Zealand, demonstrate that large body size is a significant predictor of success in rugby union. Rugby has become a fast-moving and high intensity gladiator sport, featuring big tackles and giant players. This could have a great impact on the game in the future and especially the players are going to feel the effects of injuries later in life.